Detection of Phishing Attacks on Websites with Lasso Regression, Minimum Redundancy Maximum Relevance Method, Machine Learning Methods, and Deep Learning Model - Toğaçar, Mesut (My University, 2021)
Phishing attacks are malicious software designed to steal personal or public. These types of attacks generally use e-mail addresses or aim to impersonate web-based pages to trap users. In such applications, they use textual or visual-based attractive content to lure users into their network. The internet environment is a large network platform with billions of users, and on this platform, users must be able to safely conduct their transactions without being harmed. To ensure the security of web pages simultaneously on a platform with billions of users, artificial intelligence-based software has been developed recently and this situation continues. In this study, analyzes were performed using two datasets. The two datasets consist of a total of 12454 website content. The first dataset consists of 11054 websites and the second dataset consists of 1400 websites. The datasets are divided into two classes, \"phishing\" and \"legitimate\". The contributions of machine learning methods, deep learning models, and feature selection methods in detecting phishing attacks were analyzed. The best accuracy success rate for the first dataset was 97.26%. The best accuracy success rate for the second dataset was 94.76%. As a result, it has been observed that feature selection methods contribute to the experimental analysis in general.
Keywords: Machine learning; deep learning; Phishing attack; feature selection.